The Impact of Swimming on the Human Body and the Long-Term Physiological Consequences of The Sport - A Literature review - Szaryński, Mikołaj; Gólcz, Adrian; Kadłubowska, Karolina; Chojnowska, Natalia; Rytel, Jan; Jakubowska, Martyna; Bursztyn , Tomasz; Jakubowska, Paulina; Gólcz, Julia; Sikorski, Adam; et al. (Quality in Sport, 2025)
Swimming is a comprehensive form of physical activity that provides significant physiological and psychological benefits. This review analyzes data from studies conducted between 1990 and 2024 concerning the effects of swimming on cardiovascular and respiratory function, musculoskeletal health, metabolism and mental well-being. Regular swimming enhances cardiac output, pulmonary function and muscle strength while supporting favorable metabolic adaptations such as improved lipid profiles and insulin sensitivity. Although it has a limited effect on bone mineral density compared to weight-bearing activities, it contributes to overall musculoskeletal stability and functional fitness. Furthermore, swimming reduces stress, anxiety and depressive symptoms, and supports cognitive health by preserving hippocampal volume in older adults. Long-term engagement in swimming is associated with improved mobility, reduced fall risk and lower all-cause mortality, confirming its role as an effective strategy for promoting longevity.